2013
DOI: 10.1002/col.21826
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and modeling between color variation and quality of the surface between accelerated and natural tropical weathering in Acacia mangium, Cedrela odorata and Tectona grandis wood with two coating

Abstract: To prevent the photodegradation process, a wide range of coatings have been developed. This study evaluated wood color change (DE*) and the surface quality index (SQI) generated by ASTM D-660 standards in wood protected with polyurethane and varnish finishes of three tropical species (Acacia mangium, Cedrela odorata and Tectona grandis) in two weathering conditions (natural and accelerated condition). In addition, a model was developed to predict DE* and SQI in natural weathering based on DE* and SQI from acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…In this study, the overall results of color preferences test revealed that respondents expressed a stronger preference for the darker color of Cui et al (2004) and Valverde and Moya (2014): (1) negligible: ΔE* between 0 to 0.5; (2) slightly perceivable: ΔE* between 0.5 to 1.5; (3) noticeable: ΔE* between 1.5 to 3.0; (4) appreciable: ΔE* between 3.0 to 6.0; (5) very appreciable: ΔE* between 6.0 to 12.0; and (6) totally changed: ΔE* more than 12.0. …”
Section: Consumer Preferences Towards Colors Of Heat-treated Woodssupporting
confidence: 48%
See 1 more Smart Citation
“…In this study, the overall results of color preferences test revealed that respondents expressed a stronger preference for the darker color of Cui et al (2004) and Valverde and Moya (2014): (1) negligible: ΔE* between 0 to 0.5; (2) slightly perceivable: ΔE* between 0.5 to 1.5; (3) noticeable: ΔE* between 1.5 to 3.0; (4) appreciable: ΔE* between 3.0 to 6.0; (5) very appreciable: ΔE* between 6.0 to 12.0; and (6) totally changed: ΔE* more than 12.0. …”
Section: Consumer Preferences Towards Colors Of Heat-treated Woodssupporting
confidence: 48%
“…The colorimetric evaluation was performed using the CIE-Lab system (Esteves et al, and the overall color change (ΔE*) were calculated using the following equations, The values of color changes (ΔE*) were then used to define the levels of perceived difference in color (Cui et al, 2004;Valverde and Moya, 2014). ΔE* between 0 to 0.5 is defined as negligible, between 0.5 to 1.5 is slightly perceivable, between 1.5 to 3.0 is noticeable, between 3.0 to 6.0 is appreciable, between 6.0 to 12.0 is very appreciable, and more than 12.0 is totally changed.…”
Section: Color Evaluationmentioning
confidence: 99%
“…The levels of perceived difference in color were determined according to Cui et al (2004) and Valverde and Moya (2014), which are as follows: (1) ΔE* between 0 to 0.5 is defined as negligible; (2) ΔE* between 0.5 to 1.5 is slightly perceivable; (3) ΔE* between 1.5 to 3.0 is noticeable; (4) ΔE* between 3.0 to 6.0 is appreciable; (5) ΔE* between 6.0 to 12.0 is very appreciable; and (6) ΔE* more than 12.0 is totally changed.…”
Section: Board Evaluationmentioning
confidence: 99%
“…The degradation of the coating system on wood's surface differs depending on the climate conditions (Creemers et al 2002;Valverde and Moya 2014), wood species, and other factors. Therefore, it is necessary to test selected coatings on various woods in different regions.…”
Section: Introductionmentioning
confidence: 99%